Rapid response events with multiple triggers are associated with poor outcomes in children - Kritz, Erin M.; Thomas, Jenilea K.; Alawa, Nawara S.; Hadad, Elit B.; Guffey, Danielle M.; Bavare, Aarti C. (Frontiers in Pediatrics, 2023)
Objective: We describe the characteristics and outcomes of pediatric rapid response team (RRT) events within a single institution, categorized by reason for RRT activation (RRT triggers). We hypothesized that events with multiple triggers are associated with worse outcomes. Patients and Methods: Retrospective 3-year study at a high-volume tertiary academic pediatric hospital. We included all patients with index RRT events during the study period. Results: Association of patient and RRT event characteristics with outcomes including transfers to ICU, need for advanced cardiopulmonary support, ICU and hospital length of stay (LOS), and mortality were studied. We reviewed 2267 RRT events from 2088 patients. Most (59%) were males with a median age of 2 years and 57% had complex chronic conditions. RRT triggers were: respiratory (36%) and multiple (35%). Transfer to the ICU occurred after 1468 events (70%). Median hospital and ICU LOS were 11 and 1 days. Need for advanced cardiopulmonary support was noted in 291 events (14%). Overall mortality was 85 (4.1%), with 61 (2.9%) of patients having cardiopulmonary arrest (CPA). Multiple RRT trigger events were associated with transfer to the ICU (559 events; OR 1.48; p<0.001), need for advanced cardiopulmonary support (134 events; OR 1.68; p <0.001), CPA (34 events; OR 2.36; p=0.001), and longer ICU LOS (2 vs 1 days; p<0.001). All categories of triggers have lower odds of need for advanced cardiopulmonary support than multiple triggers (OR 1.73; p<0.001). Conclusions: RRT events with multiple triggers were associated with cardiopulmonary arrest, transfer to ICU, need for cardiopulmonary support, and longer ICU LOS. Knowledge of these associations can guide clinical decisions, care planning, and resource allocation.